2022
DOI: 10.1007/s11469-022-00921-y
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Alcohol Use: a Nationwide Study in a Multiethnic Population

Abstract: The increase in alcohol consumption, and the greater consequences of chronic alcohol use among females, as well as the convergence of the gender gap warrants investigation. This paper aims to uncover gender differences in individuals with alcohol use disorder (AUD) in Singapore. The SMHS 2016 was a population-based, cross-sectional, epidemiological study. Recruitment spanned from August 2016 to March 2018, where 6126 respondents were recruited. Similarly to global estimates, lifetime prevalence and 12-month pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 43 publications
2
6
0
1
Order By: Relevance
“…The HC group is characterized by a high number of female subjects while the AUD sample contained mostly male participants. Concerning the AUD sample, our numbers reflect the epidemiological situation as men are diagnosed with AUD about four times as often as women ( 55 ). However, it has been repeatedly shown, that PIT effects are not affected by confounders such as age or gender ( 42 ).…”
Section: Discussionmentioning
confidence: 60%
“…The HC group is characterized by a high number of female subjects while the AUD sample contained mostly male participants. Concerning the AUD sample, our numbers reflect the epidemiological situation as men are diagnosed with AUD about four times as often as women ( 55 ). However, it has been repeatedly shown, that PIT effects are not affected by confounders such as age or gender ( 42 ).…”
Section: Discussionmentioning
confidence: 60%
“…In our review, we found limited countries providing data on the prevalence of the last 12‐month AUD, ranging from 1.0% in Iran to 11.2% in Lebanon and Tunisia. Compared globally, the corresponding estimate is as high as 13.6% in the United States and 20.9% in the Russian Federation [1], and as low as 0.8% in Singapore [34] and 0.9% in Japan [35]. Thirteen countries reported alcohol as the primary substance among treatment‐seeking people who use substances, resulting in a pooled estimate of 17% for alcohol being the primary substance.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of our study is the absence of a female cohort; these studies are currently underway, but further investigation is needed. While clinical AUDs affect males disproportionately more than females [52], females, in several pathological measures, have worse health outcomes related to alcohol-induced damage [53]. Given the limited existing data and knowledge on reversal of cardiac damage with abstinence, we chose to initially concentrate on a male cohort to establish a foundational understanding before potentially expanding our investigation to include female animals.…”
Section: Discussionmentioning
confidence: 99%